'Hang on a Minute, I've Got a Great Idea': From the Third Way to Mutual Advantage3 in the Political Economy of the British Labour Party. (28th August 2012) - Rogers, Chris
<x xml:space="preserve">Abstract</x> The article considers the reasons why New Labour's political economy failed to insulate Britain from the economic crisis that emerged in 2007, and the characteristics of a political economy platform that would provide Labour with a solid base for a progressive social democratic programme moving forward. The article argues that Third Way political economy failed to appreciate or address the inherent crisis dynamics of market economies, especially the extent to which profit‐seeking behaviour tends to contradict social interests more broadly conceived. The article argues that mutual organisation offers an opportunity to mute the crisis dynamics in capital by re‐establishing links between production and community, and that the Labour party should seize on this opportunity at a moment of crisis to form the basis of a progressive programme of social democratic reform.